Einsatz und Nutzen von Gesundheits-Apps in chirurgischen Disziplinen: ein Delphi-Experten-Konsensus - Groeben, Christer; Karschuck, P.; Kormann, F.; Baunacke, M.; Wiemer, L.; Krause, Hannah; Fuchs, K.; Wiedemann, A.; Schnitzbauer, A. A.; Schmitz, A.; Ebert, D.; Struck, J. P.; et al. (Die Chirurgie, 2025)
Background Healthcare apps or healthcare applications (DiHA) offer great potential for the modernization of healthcare treatment but place high demands on the digital health landscape. In order to achieve a real additional value for the treatment of patients, clear criteria must be fulfilled. This article is based on a consensus conference of the Digital Health Summit (29-30 August 2024) at the Technical University Brandenburg. Material and method A modified multistage Delphi survey procedure was carried out with interdisciplinary experts from clinical, scientific and industrial sectors to achieve a consensus on the requirements for surgical healthcare apps. Results The Delphi procedure led to 30 statements on requirements for surgical apps in Germany. They can provide evidence-based benefits for patient information and reduction of symptoms but must be more stringently tested in clinical studies on benefits and safety. In addition, apps can support training, simplify documentation and organize processes more efficiently. Uniform quality criteria are necessary in the European context. Patient data should be anonymized to assist research, whereby the sovereignty of the data lies by the patients. Regulatory hurdles should be dismantled and DiHAs should be classified according to the evidence and the risk-benefit profile. Conclusion In our statements we recommend to actively promote the development and use of healthcare apps to improve the treatment of patients in surgery. This requires targeted support for licensing, research and use, particularly by academic groups, as well as studies on the efficacy of healthcare apps.